2014
DOI: 10.1193/030713eqs066m
|View full text |Cite
|
Sign up to set email alerts
|

Select Liquefaction Case Histories from the 2010–2011 Canterbury Earthquake Sequence

Abstract: The 2010–2011 Canterbury earthquake sequence began with the 4 September 2010, Mw7.1 Darfield earthquake and includes up to ten events that induced liquefaction. Most notably, widespread liquefaction was induced by the Darfield and Mw6.2 Christchurch earthquakes. The combination of well-documented liquefaction response during multiple events, densely recorded ground motions for the events, and detailed subsurface characterization provides an unprecedented opportunity to add well-documented case histories to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…15d. Green et al (2014) identified sand layer 1 as the critical layer, yet the analyses also showed a thinner and shallower sandy layer that has a high probability of liquefaction. For both layers, the threshold YSR approach clearly recognizes these two sand layers as contractive.…”
Section: Cyclic Liquefaction Example -Christchurchmentioning
confidence: 94%
See 1 more Smart Citation
“…15d. Green et al (2014) identified sand layer 1 as the critical layer, yet the analyses also showed a thinner and shallower sandy layer that has a high probability of liquefaction. For both layers, the threshold YSR approach clearly recognizes these two sand layers as contractive.…”
Section: Cyclic Liquefaction Example -Christchurchmentioning
confidence: 94%
“…A selected liquefaction case study at Site 19 in Brighton, a suburb of Christchurch, New Zealand that had experienced damages during the 2010-2011 sequences of large earthquakes will be used for illustration. Full details on the liquefaction site are given in Green et al (2014) and a quick summary of the post-processing of the CPTu sounding is presented in Fig. 15.…”
Section: Cyclic Liquefaction Example -Christchurchmentioning
confidence: 99%
“…2, 22 February 2011 Christchurch earthquake (e.g. Green et al, 2014). Ground motions from these events were recorded by a dense network of strong motion stations (e.g.…”
Section: Data and Methodsologymentioning
confidence: 99%
“…R&W98, MEA06 and I&B08), the peak ground accelerations (PGAs) at the ground surface were computed using the robust procedure discussed in detail by Bradley (2013a) and used by Green et al (2011Green et al ( , 2014 and Maurer et al (2014). The Bradley (2013a) procedure combines unconditional PGA distributions estimated by the Bradley (2013b) ground motion prediction equation, recorded PGAs from strong motion stations, and the spatial correlation of intra-event residuals to compute the conditional PGA distribution at sites of interest.…”
Section: Liquefaction Severitymentioning
confidence: 99%
See 1 more Smart Citation